Il ruolo di sacerdoti Camilliani nella cura di persone vittime di pratiche di contenimento e/o reclusione a causa di malattia mentale nell’isola di Flores in Indonesia - Colucci, Erminia; Prastyani, Ade W; Setiyawati, Diana (TransCulturale, 2022)
In this ethnographic excerpt, the researchers describe their experience in Flores island Indonesia, where they collected visual testimonies on the role that local Camillian priests play in the care of people dealing with severe mental illness subjected to a practice of containment and/or imprisonment known as ‘pasung’ in bhasa Indonesia. This excerpt is part of a comparative study carried out in Ghana and Indonesia focused on exploring, through visual ethnography and participatory video, examples of collaborations between mental health professionals and traditional or faith-based healers to extrapolate what are the factors and dynamics that support such collaborations and contribute to eradicating the violation of the human rights towards people suffering with mental disorders. This excerpt provides an example from one of the few Catholic communities present in Indonesia.